CAVITATION MECHANISM OF FORMATION OF NANO- AND MICROSIZE PARTICLES OF MINERALS IN ORE DEPOSITS - Adushkin V.V.; Popel S.I.; Andreev S.N. (My University, 2004)
Cavitation is shown to be a rather common and important physical effect in the processes of formation of nano- and microsize particles of natural origin. We tested the so-called cavitation hypothesis of the formation of mineral microspherules 10-100 μm in size on the basis of a cavitation model that takes into account the characteristic values of the radius of a cavitation bubble and its evolution and thermal interaction with a solid mineral particle placed inside the bubble. We demonstrate that the model explains the appearance of the microspherules in accordance with the data of observations. An analogous cavitation mechanism can lead to the formation of mineral nanospherules in hydrothermal fluids. Another mechanism that can result in the formation of mineral nanospherules is the ablation process. This process is realized as a release into the ambient fluid of a superheated layer taking the form of small nanosize drops of melted substance in the case when the temperature in the compressing cavitation bubble exceeds the boiling temperature of the substance of the drops, the boiling temperature corresponding to the external pressure in the hydrothermal fluid. We discuss the conditions of experiments on melting of refractory materials in the process of their interaction with cavitation bubbles; such experiments are important from the viewpoint of identification of mechanisms of formation of mineral nano-and microspherules in the Earth's crust.